2016
DOI: 10.2217/fmb-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Flagellin Protects against Acute Pneumococcal Pneumonia in a TLR5-Dependent and NLRC4-Independent Fashion

Abstract: Ligation of TLR5, a pathogen recognition receptor not naturally engaged by pneumococcus, protects mice from invasive pneumonia when administered via sublingual route. This can be a highly cost-effective alternative therapy against pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…It is noteworthy that flagellin was found to be very effective in activating neonatal lung antigen-presenting cells (40). Furthermore, flagellin-TLR5 activation was observed to protect mice from invasive pneumonia through early clearance of Pseudomonas aeruginosa in respiratory epithelial cells (2,32). These studies support the concept that flagellin or pharmacological TLR5 agonists (i.e., entolimod, currently under clinical trials) can be redirected as a potent therapeutic to eliminate SARS-CoV-2.…”
supporting
confidence: 57%
“…It is noteworthy that flagellin was found to be very effective in activating neonatal lung antigen-presenting cells (40). Furthermore, flagellin-TLR5 activation was observed to protect mice from invasive pneumonia through early clearance of Pseudomonas aeruginosa in respiratory epithelial cells (2,32). These studies support the concept that flagellin or pharmacological TLR5 agonists (i.e., entolimod, currently under clinical trials) can be redirected as a potent therapeutic to eliminate SARS-CoV-2.…”
supporting
confidence: 57%
“…Furthermore, the administration of TLR5 agonist (flagellin) enhances the IL-22 production from group 3 ILCs during S. pneumoniae-induced pneumonia ( Figure 2B). Studies have also shown earlier, the protective action of mucosal (including sublingual root) flagellin administration to mice infected with S. pneumoniae-induced pneumonia without the activation of NLRC4 inflammasome (138,139). Also, the TLR5 agonist (flagellin) administration increases the efficacy of antibiotic treatment during pneumonia (140).…”
Section: Pulmonary Innate Lymphoid Cells (Ilcs) During Pneumonia and mentioning
confidence: 91%
“…Mucosal administration of flagellin conferred resistance to S. pneumoniae lung infection whereby flagellin treatment increased bacterial clearance which was associated with increased neutrophil mobilization independent of B- and T-cells ( 120 ). More recently, this research group showed that sublingual administration of flagellin also effectively protects against pneumonia ( 85 ). Demonstrating cross-protection, treatment with bacterial flagellin was able to prevent infection with or cure ongoing infection of rotavirus in mice independent of adaptive immunity ( 84 ).…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%